Årbog for Dansk Skolehistorie, 1967 - Grosen, Uffe (Grundtvig-studier, 1969)
Yearbook for dansk Skolehistorie, 1967 Reviewed by Uffe Grosen.Selskab for dansk Skolehistorie was formed in 1966 and aims at publishing important contributions to the elucidation of school history in the wide sense of this word. Research in this field comes within the province of the Institut for dansk Skolehistorie, established in 1965 in close connection with “ Danmarks Lærerhøjskole”. In the first year-book ( 1967) of the Society dr. phil. Roar Skovmand gives an account of the inherent problems of a research which has since 1899 been less than adequate. In this connection he discusses the critical analysis of interviews with people who are still alive. In a picture of the Danish school Grundtvig next to Georg Brandes will play a role similar to that of Plato and Aristotle in the famous “ School of Athens” by Raphael. The reviewer misses some clearly drawn portraits here, however, for instance of Ludv. Chr. Müller and P. J. M. Vinther, portraits which might contribute to a heightened interest in the inner life of the school. - In a survey of the contents of the “ Stiftsmuseum” of Lolland Falster pertaining to educational history the museum keeper Else-Marie Boyhus gives an excellent illustration of the aims of the Society. - How the Swedish Society Föreningen för svensk undervisningshistoria, established in 1920, meant a stimulus to the formation of the Danish Society is the subject of an article by dr. theol. Knud Eyvin Bugge, who is also the editor of a part of Grundtvig’s curious early work, the comedy Skoleholderne from the summer of 1802. - Skolen for livet ( 1963), K. E. Bugge’s thesis for the doctorate, is reviewed in an article by William Michelsen, a theoretical treatment of the subject “ Education and Outlook”. - The centre of gravity of the year-book is the account, by mag. art. Kai Hørby, of Grundtvig’s struggle to establish “ The High-School in Soer”, which all but succeded and yet came to nothing. As the reviewer points out the management of the High-School was to be a copy of the absolute rule of the country, but with an advisory organ attached, and Grundtvig expected it to be attended by the brightest and maturest minds among Danish youth, students with an urge to receive education and with a sense of responsibility. — An article dealing with “ The Political Debate about the Connection between Board School and Grammar School”, by cand. mag. Vagn Skovgaard-Petersen, illustrates how the Grundtvigian point of view, a self-contained children’s school, suffered defeat in spite of very capable spokesmen. The author concludes with the important remark, however, that Grundtvigian efforts on behalf of the undivided children’s school were continued after 1903—“as we know not unsuccessfully”. Readers will be looking forward to see whether this fine year-book is going to have equally worthy successors.